AN ANALYSIS OF THE MAIN CHARACTERS’ MORAL RESPONSIBILITY IN THE FILM GRAVE OF THE FIREFLIES - Chintya Dini Aprilianty; Nuriadi Nuriadi; Atri Dewi; Azis Baharuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
As time progresses, many literary works have been adapted into films, including animated films that often present moral values. One animated film that portrays moral values is Grave of the Fireflies by Isao Takahata. This study aims to analyze the forms of moral responsibility expressed by the main characters in Grave of the Fireflies. The research employs a qualitative method, using dynamic structuralism theory that examines the interrelationships among the elements of the story as a whole through two types of analysis: intrinsic analysis (characterization of the main characters, plot and conflict) and extrinsic analysis (Japanese cultural values). Furthermore, the analysis is supported by moral responsibility theory to identify and describe the forms of moral responsibility portrayed by the main characters. The results revealed that the main characters moral responsibility in this film is divided into two main forms. The first is Protective and Practical Responsibility, reflected in Seita’s decision to care for and protect his younger sister, Setsuko. The second is Existential Moral Responsibility, evident in his decision to leave his aunt’s house and the moral consequences that arise from his actions. These two forms of responsibility highlight the strong influence of Japanese cultural values (bushidō and giri) that emphasize honor, loyalty, sacrifice, and moral obligation toward the family. These findings highlight that Grave of the Fireflies not only portrays the destructive impact of war but also presents a profound reflection on humanity and moral responsibility within the context of Japanese culture.